The Importance of Proper History Taking: Asking a Fever Pattern in Patients with Vivax Malaria - Chang, Euijin (J Korean Med Sci, 2020)
Characteristic fever patterns of malarial infection are clues for diagnosis. However, checking fever patterns in febrile patients has been usually missed, and unnecessary tests have been performed. We reviewed electrical medical record to check whether history-taking included questions on fever pattern in febrile patients. Main outcomes were time interval between visit and diagnosis of vivax malaria and proportion of patients who had taken unnecessary tests. Among 134 vivax malarial patients, asking about fever pattern was done in 64 (47.8%). Median time interval between visit and diagnosis was significantly shorter in patients whose fever pattern was asked than those not asked (3.2 hours vs. 18.6 hours; P < 0.001). Unnecessary diagnostic tests were conducted in 27% (17/64) of patients asked about fever pattern and 71% (50/70) in patients not asked (P < 0.001). Proper history-taking can reduce time elapsed for diagnosis and performing unnecessary diagnostic tests in vivax malaria.